Phage–host interplay: examples from tailed phages and Gram-negative bacterial pathogens - Chaturongakul, Soraya; Ounjai, Puey (Frontiers in Microbiology, 2014)
Complex interactions between bacteriophages and their bacterial hosts play significant roles in shaping the structure of environmental microbial communities, not only by genetic transduction but also by modification of bacterial gene expression patterns. Survival of phages solely depends on their ability to infect their bacterial hosts, most importantly during phage entry. Successful dynamic adaptation of bacteriophages when facing selective pressures, such as host adaptation and resistance, dictates their abundance and diversification. Co-evolution of the phage tail fibers and bacterial receptors determine bacterial host ranges, mechanisms of phage entry and other infection parameters. This review summarizes the current knowledge about the physical interactions between tailed bacteriophages and bacterial pathogens (e.g., Salmonella enterica and Pseudomonas aeruginosa) and the influences of the phage on host gene expression. Understanding these interactions can offer insights into phage-host dynamics and suggest novel strategies for the design of bacterial pathogen biological controls.